Effect of heat treatment with antioxidants on respiratory substrates during storage of cucumbers - Прісс, Олеся Петрівна (Eastern-European Journal of Enterprise Technologies, 2015)
Despite the proven effectiveness of heat treatment and antioxidants to slow down the respiratory metabolism, their combined effect during storage of cucumbers was not considered in this aspect. The paper describes the results of investigating the effect of heat treatment with complex antioxidant on respiration rate and expenditure of solids, soluble solids, sugars and titrated acids during storage of cucumbers. It was found that heat treatment with antioxidants inhibits the respiration rate and suspends the start of the respiration rate increase by 7 days compared with control fruits. The combination of heat treatment and antioxidants allows to obtain by on average 11 % more solids and 13 % more soluble solids on the 21th day of storage. Cucumbers, treated with antioxidants involve less sugar in the respiratory process. After 21 days of storage, the total amount of sugars in study fruits of the Athena hybrid is higher on average by 12 %, and in Masha cucumbers - by 42 % compared with control fruits. Based on the pair correlation analysis, it was found that acids can be a major respiratory substrate during storage of cucumbers. The combination of heat treatment and antioxidants can be an effective tool to reduce the loss of nutrients during storage of cucumbers.